2007
DOI: 10.1074/jbc.m700188200
|View full text |Cite
|
Sign up to set email alerts
|

Polyinosinic Acid Is a Ligand for Toll-like Receptor 3

Abstract: Innate immune responses are critical in controlling viral infections. Viral proteins and nucleic acids have been shown to be recognized by pattern recognition receptors of the Toll-like receptor (TLR) family, triggering downstream signaling cascades that lead to cellular activation and cytokine production. Viral DNA is sensed by TLR9, and TLRs 3, 7, and 8 have been implicated in innate responses to RNA viruses by virtue of their ability to sense double-stranded (ds) RNA (TLR3) or singlestranded RNA (murine TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 28 publications
(34 reference statements)
3
70
0
Order By: Relevance
“…pp , 0.05 compared with stimulated controls using a MannWhitney U test. 41). We believe that our data demonstrate a further mechanism through which progesterone could be functioning to limit the antiviral response by reducing TLR3-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…pp , 0.05 compared with stimulated controls using a MannWhitney U test. 41). We believe that our data demonstrate a further mechanism through which progesterone could be functioning to limit the antiviral response by reducing TLR3-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…26 We utilized polyinosinic acid (polyI) a synthetic polyanionic ligand for SR-A/MARCO that also stimulates intracellular TLR3 to release inflammatory cytokines. 28 Similarly, the bacterial cell wall product muramyl dipeptide (MDP) stimulated the cytosolic sensor NOD2, and silica, asbestos, and a combination of NM and extracellular ATP stimulated NALP3 inflammasomes and engaged SR-A and MARCO. 29,30 We show that SR-A/MARCO competes with TLR4 for ligand recognition, limiting its inflammatory response, but strikingly enhances TLR3-, NOD2-, and NALP3-mediated inflammatory responses.…”
mentioning
confidence: 99%
“…To investigate how SR-A and MARCO modulate the inflammatory response by intracellular TLR3, which signals independently of MyD88, we utilized polyI, a synthetic polyanionic ligand for SR-A, MARCO, and intracellular TLR3. 28 WT, SR-A Ϫ/Ϫ , MARCO Ϫ/Ϫ , and DKO macrophages were stimulated with polyI, and secretion of cytokines was measured. Results showed that polyI induced TNF-␣ and IL6 in WT M as expected, but cytokine secretion was almost completely abolished in SR-A Ϫ/Ϫ and DKO macrophages.…”
mentioning
confidence: 99%
“…In some cases, the mode of delivery, for example transfection versus addition to media, also influences the response [24], which may be due to effects on localization of the ligand within the cell as well as the amount of ligand taken up. TLR3 is commonly located in endosomes and recognizes double-stranded RNA and its mimic poly(I:C) [25], and more recently it was shown to also recognize single-stranded poly(I) [26]. RIG-I and MDA5 are cytoplasmic RNA helicases originally identified as double-stranded RNA receptors [10]; however, RIG-I was shown to recognize single-stranded RNA with 5′ triphosphates [27,28].…”
Section: Discussionmentioning
confidence: 99%